A Critical Analysis of a Chapter From an EFL Textbook : a TBLT Perspective - Suherman, Andri (Universitas Hamzanwadi, 2018)
This research article aimed to analyze tasks employed in an Indonesian EFL textbook from the perspective of TBLT approach. The analysis involved chapter eight in the EFL textbook of grade ten. Meanwhile, the six features of a task proposed by Ellis (2003) were used to analyze the tasks. The findings revealed two points; (1) none of the fifteen tasks in the chapter employed the six crucial features of a task, (2) all the fifteen tasks in the chapter were potential to change to be more task-like. The implication of this study was to provide insight to EFL material developers to be more aware of the task features, and to offer suggestions to EFL education practitioners in redesigning existed tasks to be more task-like.